Characteristics and dynamics of sediment at Marudu Bay, Sabah, Malaysia - Muhammad Rashid Abdul Rahim (2019)
Marudu Bay lies between the geographical coordinates of 6.9511 °N - 7.0373°N and 116.7420 °E - 117.0339 °E where some part of the Bay is under the Tun Mustapha Park (TMP) area that has been gazetted as Malaysia's largest marine protected area. Rapid coastal development and land clearing for aquaculture activities leads to high sediment discharges that may affect the Bay by damaging its marine resources. Hydrodynamic factor plays an important role in the movement of the sediment within the Bay, and it is affected by river discharge, geomorphology of the bay, bathymetry and tidal constituent. The current study aimed to identify the grain size, distribution, and characteristic of surface sediment at the seabed in inner and outer part of Marudu Bay during northeast, inter-, and southwest monsoon. These data then were simulated for hydrodynamic and sediment dynamic during northeast monsoon via Delft3D simulation model. The model set-up of Delft3D simulation was calibrated and verified using field measurements of data, such as water level, current speed and current direction. The field data for current verification were measured using Acoustic Wave and Current profiler deployed on 12 - 25 March 2015 in the middle of the Bay. The surface sediment and water samples were collected at specific date from 45 stations within the Bay using Ponar grab and horizontal water sampler. Subsequently, the sediment and water samples were then analysed using the LISST-Portable Laser Diffraction Size Analyser and standard method in determination of Total Suspended Sediment (TSS), respectively. The composition of silt and sandy silt (7.92 - 68.18 µm) content in the surface sediment samples from entire Marudu Bay (n=38) was dominant with about 90 % and 40 %, respectively. Sand and silty sand (94.94 - 250 µm) composition present only at the certain area (n=7) with 98 % and 80 %, respectively. Highest TSS value was found at ST26 with 14.1 mg/L which located near Telaga river. Overall from 45 sediment samples obtained at Marudu Bay, for sorting characteristic group; (i) 43 samples were poorly sorted and 2 were well sorted, (ii) 33 samples were under coarse skewed and another 12 under fine skewed, and (iii) 38 samples under mesokurtic and 7 under leptokurtic. The hydraulic movement during the ebb and flood tide were uniforms where the water enters and out from the Bay through Cape of Simpang Mengayau. During spring ebb tide (-0.58 m) the surface sediments from inner and outer part of the Marudu Bay were transported out at the rate of 0.1x106 to 0.2x106 m3/s/m and 0.2x106 to 0.4x106 m3/s/m with a mean current speed of 0.13 m/s. While during spring flood tide (0.28 m), the surface sediments were transported into the Bay at the rate of 0.4x106 to 1.8x106 m3/s/m with a mean current speed of 0.09 m/s. Usage of silt curtain need to be implemented as mitigation measure to minimize the sedimentation. Findings of this present study provide baseline information on sediment transport and hydrodynamic pattern within the Marudu Bay to decisionmakers in developing sustainable aquaculture activities.